Migration of a Distal Ventriculoperitoneal Shunt Catheter Into The Internal Jugular Vein – A Case Report - Skalický, Petr; Bubeníková, Adéla; Leško, Róbert; Haratek, Kryštof; IIIrd, Vladimír Beneš; Bradáč, Ondřej (Annapurna Journal of Health Sciences, 2025)
A rare case of migration of the distal ventriculoperitoneal (VP) shunt catheter into the internal jugular vein is presented with its resolution by a conversion to a ventriculoatrial (VA) shunt. A 75-year-old female patient underwent a near-total surgical resection of a left vestibular schwannoma (grade 4b) while the postoperative period was complicated by acute decompensation of secondary normal pressure hydrocephalus. Subsequently performed VP shunt procedure was complicated by convolution of the distal catheter in the abdominal subcutaneous tissue with a collection of fluid and developed loop of the VP shunt course in the cervical region. Despite surgical revision, distal catheter completely migrated into the internal jugular vein. As a result, surgical conversion of the VP shunt to the VA shunt was successfully performed. Follow- up period was uneventful, and the patient is able to independently carry out ordinary daily activities Tunneling procedure through the supraclavicular region is associated with a risk of direct vein damage. Conversion to a VA shunt represents an effective solution of VP shunt migration into the internal jugular vein with the need for its early detection and prompt treatment.